Pengajaran Moderasi Beragama di Pesantren dalam Menghadapi Era Society 5.0. - Vita Fitriatul Ulya; Moh. Subhan (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This research is done because the increasing cases of intolerance in Indonesia. As a diverse country where Islam is the largest religion, Islamic educational institutions play a crucial role in maintaining diversity to foster harmony and peace. Pesantren, as one of the Islamic educational institutions, contributes to teaching a moderate religious attitude. The aim of this research is to understand and explore the teaching of religious moderation in pesantren in relation to the challenges faced by students in the era of society 5.0. This study adopts a qualitative descriptive approach with literature research as the research type. Data were collected through academic journal articles published in the last 5 years and online news related to religious moderation, pesantren, and the era of society 5.0. The results indicate that the advancements and technological sophistication in the era of society 5.0 have both positive and negative impacts on human life. The negative effects include changes in human thought and lifestyle in social and religious aspects. As a pluralistic nation, Indonesia needs to maintain the unity of its religious communities in accordance with the principles of Pancasila. Furthermore, pesantren, as one of the Islamic educational institutions, plays a vital role in teaching a moderate religious attitude in the era of society 5.0. One of the forms of teaching is through the internalization of values such as justice, harmony, and unity in the learning of the Quran and traditional Islamic texts in pesantren.